PRODUKSI GAS IN VITRO ASAM AMINO METIONIN TERPROTEKSI DENGAN SERBUK MIMOSA SEBAGAI SUMBER CONDENSED TANNIN (CT) - amiril mukmin; Hendrawan Soetanto; Kusmartono Kusmartono; Mashudi Mashudi (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2014)
The aim of this research was to evaluate the effect mimosa powder as CT source to protect methionine from degradation using in-vitro gas production technique. Four treatments were assigned in a Randomized Block Design: T0 = methionine + 0% CT; T1 = methionine + 6% CT; T2 = methionine + 8% CT; T3 = methionine + 10% CT. Gas production was measured at time intervals and terminated after 48 hour incubation. The results showed that gas production was decreased as the level CT increased. The corresponding values for gas production at 48 hour were respectively 23.58 ml/500mg (P0); 22.37 ml/500mg (P1); 21.54 ml/500mg (P2); and 20.62 ml/500mg (P3). It can be concluded that mimosa powder can be used as CT source to protect methionine from rumen microbes degradation. It is suggested to do further studies on the effect of adding protected methionine in a complete ration on animal production. Keyword: Methionine, condensed tannin (CT), in-vitro gas production